The impact of weight change and measures of physical functioning on mortality. Issue 4 (6th January 2022) - Underland, Lisa J.; Schnatz, Peter F.; Wild, Robert A.; Saquib, Nazmus; Shadyab, Aladdin H.; Allison, Matthew; Banack, Hailey; Wassertheil‐Smoller, Sylvia
Abstract: Introduction: Lower grip strength and measures of physical functioning are associated with all‐cause mortality. Relationships among long‐term weight loss, physical functioning, and mortality in older women are understudied. Methods: Participants were 5039 women who were part of the Long Life Study (LLS) ancillary study to the Woman's Health Initiative (WHI). Average age was 78.76 ± 6.92. We defined long‐term weight loss or gain as a decrease or increase of 5% or more of baseline body weight. Our primary outcome was all‐cause mortality and our secondary outcomes were vascular death, and coronary heart disease (CHD). The mean follow‐up time was 5.4 years. Cox regression modeling was performed for each outcome of interest. Variables of interest were weight change, grip strength, and functional status as measured by the Short Physical Performance Battery (SPPB) controlling for multiple potential confounders. Results: Weight loss of 5% or more percent body weight was associated with a hazard ratio of 1.66 (1.37–2.01) for all‐cause mortality. Weight gain was not related to mortality or cardiovascular outcomes. Those in the highest grip strength quartile had a hazard ratio of 0.51 (0.39–0.66) for all‐cause mortality. For the SPPB the hazard ratio was 0.29 (0.21–0.40), adjusting for changes in weight, race, smoking, history CHD, smoking, and diabetes. Higher grip strength and SPPB were associated with lower risks for vascular death, and CHD, independently of weight change. Conclusions: Weight loss was associated with increased mortality. Stronger grip strength and higher SPPB scores were associated with lower mortality risk independent of weight change.